Soil-Structure Interaction - Ong, Dominic E.L; Cheng, Wen-Chieh; Zhou, Hannah (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
It is crucial that scientists and engineers develop their expertise and capability through research and practice to quantify the interaction of infrastructure with the surroundings and the ground upon which they are founded. Therefore, the engineering concept 'soil-structure interaction' forms an integral part of delivering successful project outcomes. As the Lead and Honorary Editor for this Special Issue, Soil-Structure Interaction, I cordially invited the submission of esteemed articles related to recent projects, research, or case studies. These articles detail how geosciences (soil, rock, ground water, geochemistry, geology, hydrogeology, surface run-off, rain, wind, and temperature) directly interact with and impact the performance of human-made structures, buildings, or infrastructure through the following aspects: i) Underground construction; ii) Innovative ground improvement methods; iii) Geological explorations and interpretation; iv) Instrumentation and field observational method; v) Use of artificial intelligence or algorithms; vi) Forensic engineering or inverse-analysis methods; vii) Geophysical methods for soil or rock characterization; viii) Advancement in laboratory and field testing of geomaterials; ix) Advancement in numerical analysis; x) Advancement in multi-disciplinary design theories, codes of practice, and engineering education.